Development and Acceptability of Chargeable Battery-Operated Soldering Iron Device: An Operation Guide - Reo R. Lequigan; Rowena P. Dato-on; Mailyn T. Lequigan; Ritchie L. Gahob; Roda L. Larga; Jessie M. Casia; Keith Orville S. Gahob; Vincent Gian; Jhon Felix C. Capuno; Angelito L. Marsan (The Indonesian Institute of Science and Technology Research, 2026)
This study developed a chargeable battery-operated soldering iron device and determined its level of acceptability to address unexpected power interruptions because it can be used without the presence of AC power. The study utilized a descriptive experimental approach since it developed a chargeable battery-operated soldering iron device. It was assessed with its specifications and functionalities. Survey questionnaires were used and distributed to the sixty respondents from CTU Daanbantayan Campus and San Remigio Extension Campus. It was found out that in terms of risk, perceived usefulness, perceived ease of use, attitude, and intention of use, the chargeable battery-operated soldering iron device was highly acceptable. However, respondents recommended decreasing the weight and size and putting the product in a box to make it more portable. When it comes to safety, it is also suggested to put an LED to indicate its ON/OFF status to avoid skin burns. Overall, the product was highly acceptable to be used as a soldering iron device. An operation guide was made for the users to be guided on how to use the product.